Prevalence and risk factors of Giardia duodenalis in domestic rabbbits (Oryctolagus cuniculus) in Jilin and Liaoning province, northeastern China - Jing Jiang; Jian-Gang Ma; Nian-Zhang Zhang; Peng Xu; Guangyu Hou; Quan Zhao; Xiao-Xuan Zhang (Elsevier, 2018)
Background: Giardia duodenalis is one of the most important intestinal parasites that can infect virtually all animals, including rabbits and humans. However, there is little information regarding the prevalence and genotypes of G. duodenalis in domestic rabbits in China. Methods: A total of 426 rabbit fecal samples (136 from Shenyang City, 174 from Changchun City, and 116 from Jilin City) were examined by Lugol's iodine staining with microscopy analysis, and the positive samples were genotyped at the triosephosphate isomerase (tpi) and the beta giardin (bg) gene loci using nested PCR. Results: Forty-two (9.86%) out of 426 rabbit fecal samples were G. duodenalis-positive under microscopy analysis, and the highest G. duodenalis infection rate was 23.08% on farm 6. The prevalence of G. duodenalis in rabbits from different cities ranged from 1.47% to 14.37%. Among different age groups, G. duodenalis prevalence in rabbits ranged from 5.41% to 12.58%. The prevalence of G. duodenalis in outdoor rabbits and indoor rabbits was 14.29% and 6.77%, respectively. In the present study, region and farming mode were highly correlated with G. duodenalis infection in rabbits. All 42 G. duodenalis isolates were successfully amplified and sequenced at the tpi and bg loci, and only G. duodenalis assemblage B were identified. Conclusion: This study not only further confirmed the dominance of G. duodenalis assemblage B in rabbits, but also further improved the foundation data concerning the distribution of G. duodenalis assemblages in China. Keywords: Domestic rabbits, Prevalence, Genotyping, Northern China